PENGARUH PENYULUHAN KESEHATAN TERHADAP SIKAP SISWA DALAM PENCEGAHAN GASTRITIS PADA SISWA SMP DI KOTA TANGERANG - Susilowati, Yuni Yubi; Yunita, Yunita Yunita; Winarni, Lastri Mei (Universitas Muhammadiyah Lamongan, 2021)
Preliminary Based on the results of preliminary studies that have been conducted at Miftahul Khaer Islamic Boarding School, the results are obtained (70%) or 14 out of 20 people have gastritis, (10%) or 2 other people do not know if they have gastritis, then (20%) or 4 other people do not having gastritis. Purpose to determine the effect of health education on student attitudes in the prevention of gastritis. Method This type of research is quantitative research with a Quasi-experimental research design. sampling technique using incidental sampling. The sample in this study were 140 respondents. The research instrument used a questionnaire. The results based on the Wilcoxon test showed a p-value of 0,000 <0.05, so it can be concluded that